Analysis of Filtering Techniques for Spam Email Detection - Ahuja, A (International Journal of Computer Sciences and Engineering, 2025)
Email is considered to be one of the most effective ways of communication source. It has gained attention because of the fastest and cost-effective means of source of communication. But with the enormous increase in its usage leads to its exploitation as it has become fascinated approach for the today’s businesses. Email spam is the sending of unsolicited email in bulk to the randomly selected recipients for the purpose of advertising has become a serious concern. These unwanted emails not only occupy network bandwidth and memory space for communicating but can be used by the attackers in order to steal the user’s identity. By looking at the prevailing scenarios there is a need for a solution that can manage the spam issue quite efficiently. The goal of this paper is to provide insight into an issue of spam email, and the highlight of this paper is the key findings of filtering techniques used for spam detection based on analysis of the content and non-content part of email.